Analisis Pengaruh Pendidikan Karakter, Status Sosial dan Jiwa Humanis terhadap Budaya Keselamatan dan Kesehatan Kerja (Studi Pada Universitas Pamulang) - Rahmi Hermawati; Rima Handayani; Eni Puji Astuti (Mahesa Research Center, 2020)
This study aims to determine the effect of character education and social status on the culture of Occupational Safety and Health (K3) (a study at Pamulang University). This research is a causal quantitative research (cause and effect by processing numerical data), using a survey method of data collection through distributing questionnaires to Pamulang University students of Management Study Program, by determining the sample using the Slovin formula. Data analysis used validity test analysis, reliability test, classical assumption test, multiple regression analysis, correlation coefficient analysis, determination coefficient analysis, t test, and F test. Data obtained from respondents were processed using SPSS 26. The results showed that there was an influence between character education, social status and a humanist spirit towards K3 culture. Based on the results of the study, the conclusions of the research results are as follows: the results of character education (X1), social status (X2) and a humanist spirit (X2) together have a very significant effect on the K3 (Occupational Health and Safety) culture of students in the Management Study Program at Pamulang University.